RETRACTED: Study of friction in the "textile-human" system for the ergonomic design of sustainable functional clothing - Tyurin I.N.; Getmantseva V.V.; Tashpulatov S.Sh.; Andreeva E.G. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001